Kritik Sosial dalam Pementasan Drama “Ayahku Pulang” Karya Usmar Ismail - Yuwafa Faurelio Yahya; Akhmad Fatoni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to analyze Sigmund Freud's psychoanalytic theory in the drama performance entitled Ayahku Pulang by Usmar Ismail. In this study, the author uses a qualitative method, because this study is a descriptive presentation in presenting the results of the data studied. Then, considering the breadth and depth of this research, the author uses this research method. Then the data in this study uses YouTube content from an account named Kuddus. The data in this study shows that the psychological system in Sigmund Freud's psychoanalytic theory is found in the personalities of the characters in the drama performance Ayahku Pulang by Usmar Ismail, namely the Id system in the character of Ayah (Raden Saleh), the Super ego system in the character of Ibu (Tina), Maimun and Mintarsih then, the Ego system in the character Gunarto.